The impact of tourism development on economic growth in sub-Saharan Africa - Sheilla Nyasha; Nicholas M. Odhiambo; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study examines the dynamic impact of tourism development on economic growth in subSaharan Africa (SSA) using the Generalised Method of Moments and data covering the period from 2002 to 2018. The increasingly important role of tourism and the limelight the tourism sector has been enjoying of late, on the one hand, and the lack of sufficient coverage of tourismgrowth nexus studies in Africa in general and in SSA in particular, motivated this study. Unlike most of the known panel data-based studies on tourism development and economic growth, this study has split the sub-Saharan African countries into low-income and middle-income subSaharan African countries. The results of the study show that tourism expenditure negatively affects economic growth while tourism receipts have the opposite effect in SSA. The findings are robust to the low-income sub-sample while only the effect of tourism expenditure is robust in the middle-income sub-sample.
Keywords: O10; O40; Z3; Z32; 330; Tourism Development; Economic Growth; Sub-Saharan Africa; SSA; MiddleIncome Countries; Low Income Countries; Generalised Method of Moments; GMM